Shifts in Gamma Phase–Amplitude Coupling Frequency from Theta to Alpha Over Posterior Cortex During Visual Tasks - Voytek, Bradley; Canolty, Ryan T.; Shestyuk, Avgusta; Crone, Nathan; Parvizi, Josef; Knight, Robert T. (Frontiers in Human Neuroscience, 2010)
The phase of ongoing theta (4-8 Hz) and alpha (8-12 Hz) electrophysiological oscillations is coupled to high gamma (80-150 Hz) amplitude, which suggests that low frequency oscillations modulate local cortical activity. While this phase-amplitude coupling (PAC) has been demonstrated in a variety of tasks and cortical regions, it has not been shown whether task demands differentially affect the regional distribution of the preferred low-frequency coupling to high gamma. To address this issue we investigated multiple-rhythm theta/alpha phase to high gamma amplitude PAC in two subjects with implanted subdural electrocorticographic grids. We show that high gamma amplitude couples to the theta and alpha troughs and demonstrate that, during visual tasks, alpha/high gamma coupling preferentially increases in visual cortical regions. These results suggest that low-frequency phase to high-frequency amplitude PAC is modulated by behavioral task and may reflect a mechanism for selection between communicating neuronal networks.